Blockade of prostaglandin E2 receptor 4 ameliorates peritoneal dialysis-associated peritoneal fibrosis - Luo, Qimei; Liu, Mi; Tan, Yanhong; Chen, Jinzhong; Zhang, Wei; Zhong, Shaoxin; Pan, Jianyi; Zheng, Qingkun; Gong, Lewei; Su, Lijuan; Jia, Zhanjun; Dou, Xianrui (Frontiers in Pharmacology, 2022)
Inflammatory responses in the peritoneum contribute to peritoneal dialysis (PD)-associated peritoneal fibrosis. Results of our previous study showed that increased microsomal prostaglandin E synthase-1-mediated production of prostaglandin E2 (PGE2) contributed to peritoneal fibrosis. However, the role of its downstream receptor in the progression of peritoneal fibrosis has not been established. Here, we examined the role of PGE2 receptor 4 (EP4) in the development of peritoneal fibrosis. EP4 was significantly upregulated in peritoneal tissues of PD patients with ultrafiltration failure, along with the presence of an enhanced inflammatory response. In vitro experiments showed that exposure to high glucose concentrations enhanced EP4 expression in rat peritoneal mesothelial cells (RPMCs). High-glucose–induced expression of inflammatory cytokines (monocyte chemoattractant protein-1, tumour necrosis factor α, and interleukin 1β) was significantly reduced in RPMCs treated with ONO-AE3-208, an EP4 receptor antagonist. ONO-AE3-208 also significantly decreased the expression of extracellular matrix proteins induced by high glucose concentrations. Furthermore, ONO-AE3-208 blunted activation of the NLR family pyrin domain containing 3 (NLRP3) inflammasome and phosphorylation of nuclear factor kappa B (NF-κB) (p-p65). To further investigate the functional role of EP4, ONO-AE3-208 was administrated for 4 weeks in a rat model of PD, the results of which showed that ONO-AE3-208 inhibited peritoneal fibrosis and improved peritoneal dysfunction. Additionally, inflammatory cytokines in the peritoneum of PD rats treated with ONO-AE3-208 were downregulated, in line with inhibition of the NLRP3 inflammasome and NF-κB phosphorylation. In conclusion, an EP4 antagonist reduced the development of peritoneal fibrosis, possibly by suppressing NLRP3 inflammasome- and p-p65–mediated inflammatory responses. Our findings suggest that an EP4 antagonist may be therapeutically beneficial for PD-associated peritoneal fibrosis.